Universal depinning transition of domain walls in ultrathin ferromagnets - Diaz Pardo, R. (2017)
We present a quantitative and comparative study of magnetic-field-driven domain-wall depinning transition in different ferromagnetic ultrathin films over a wide range of temperature. We reveal a universal scaling function accounting for both drive and thermal effects on the depinning transition, including critical exponents. The consistent description we obtain for both the depinning and subthreshold thermally activated creep motion should shed light on the universal glassy dynamics of thermally fluctuating elastic objects pinned by disordered energy landscapes.